Design and Construction of a Water Monitoring System at PDAM Tirta Pakuan Bogor Based on Ethernet Shield and LCD - Jonser Steven; D. Dwi P.; Jajang J; Siti Farah Fakhirah; Icha Maulidya; Asa Yuaziva (Journal of Applied Science, Technology & Humanities | JASTH, 2026)
Conventional water monitoring at PDAM Tirta Pakuan Bogor is inefficient and prone to manual errors. This study aims to design a real-time monitoring system to improve operational effectiveness and data validity. Following a four-stage methodology analysis, design, implementation, and testing the device was constructed using an Arduino Uno R3, an Ethernet Shield for stable network connectivity, an ultrasonic sensor, and a 16x2 LCD. The integration of intelligent logic in such systems is crucial for identifying optimal boundary parameters to support decision making. Results demonstrate that the device successfully provides continuous, real-time measurement data via both a web interface and a physical display, aligning with desired specifications. This digital technology support facilitates optimal monitoring through easy access to information. While minor measurement errors occur due to environmental factors, the tool significantly increases the flexibility of information access. In conclusion, the Ethernet Shield and LCD-based system enables reliable monitoring without manual intervention, though it currently requires manual web refreshing to update data.